Digital Transformation and Strategic Decision-Making: A Behavioral Perspective on Business Innovation - Ira Astriyani; Fathia; Ernawaty Usman; Jurana Jurana; Mustamin Mustamin (Yayasan Cerdas Pedia Indonesia, 2025)
This systematic literature review examines the critical role of behavioral accounting in shaping strategic decision-making within the context of organizational digital transformation and business innovation. Employing a PRISMA-based methodology, this study synthesizes scholarly evidence from peer-reviewed journals and academic databases published between 2020 and 2025, addressing how behavioral factors influence the effectiveness of strategic innovation execution in digitalized business environments. The research integrates perspectives from behavioral accounting, strategic innovation economics, technology management, and platform economics to construct a unified framework explaining competitive advantage creation through digital transformation. Key findings reveal that successful strategic innovation depends not solely on technological sophistication but critically on understanding cognitive biases, technology adoption readiness, and organizational change management capabilities. The analysis demonstrates that Economic Value Added (EVA) and Market Value Added (MVA) serve as essential metrics for validating innovation effectiveness beyond traditional accounting measures. Cognitive barriers including anchoring bias, confirmation bias, and cognitive overload systematically impede strategic execution, while dynamic capabilities and upskilling investments emerge as sources of sustainable competitive advantage. The study further establishes that platform economics in financial services, particularly peer-to-peer lending, requires careful regulatory orchestration through instruments such as Indonesia's Financial Services Authority (OJK) Regulatory Sandbox. Evidence indicates that organizations integrating behavioral accounting perspectives into digital transformation strategies achieve superior innovation outcomes, with artificial intelligence adopters demonstrating 3.1 times higher return on investment when supported by clear strategic frameworks. The research contributes theoretically by synthesizing disparate literature streams into a cohesive strategic innovation economics framework, while offering practical implications for organizations navigating digital-driven transformation. Recommendations emphasize structured risk assessment models, behavioral finance training to mitigate cognitive distortions, and ecosystem-level regulatory design to balance innovation encouragement with systemic stability.